Complete mitochondrial genome of the Korean endemic species Coreoleuciscus aeruginos holotype from Korea (Cypriniformes, Cyprinidae). Issue 3 (4th March 2021) - Kim, Kang-Rae; Song, Ha-Yoon; Kim, Yong Hwi; Park, Jong Yeon; Bang, In-Chul
Abstract: This study is the first to research report the complete 16, 563 bp mitochondrial genome of Coreoleuciscus aeruginos, which consists of 13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and a control region (D-loop). The overall base composition of the complete genome is 31.0% A, 28.04% T, 16.27% G, and 24.69% C, with a high A + T content of 59.04%. According to our phylogenetic analysis, C. aeruginos is most closely related to Coreoleuciscus splendidus .